The Cognitive Science of Religion: Implications for Theism? - Leech, David (Zygon, 2011)
Abstract. Although the Cognitive Science of Religion (CSR), a current approach to the scientific study of religion, has exerted an influence in the study of religion for almost twenty years, the question of its compatibility or incompatibility with theism has not been the subject of serious discussion until recently. Some critics of religion have taken a lively interest in the CSR because they see it as useful in explaining why religious believers consistently make costly commitments to false beliefs. Conversely, some theists have argued for the compatibility of religious belief with basic CSR results. In this article, we contribute to the incipient discussion about the worldview relevance of the CSR by arguing that while a theistic reading of the field only represents one interpretative option at most, antitheistic claims about the incompatibility of the CSR with theism look like they may be harder to maintain than first appearances might suggest.